2021
DOI: 10.3390/rs13071391
|View full text |Cite
|
Sign up to set email alerts
|

Rice-Yield Prediction with Multi-Temporal Sentinel-2 Data and 3D CNN: A Case Study in Nepal

Abstract: Crop yield estimation is a major issue of crop monitoring which remains particularly challenging in developing countries due to the problem of timely and adequate data availability. Whereas traditional agricultural systems mainly rely on scarce ground-survey data, freely available multi-temporal and multi-spectral remote sensing images are excellent tools to support these vulnerable systems by accurately monitoring and estimating crop yields before harvest. In this context, we introduce the use of Sentinel-2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…If one of the Kernel functions recommended in previous research studies (Exponential/ RBF /Squared Exponential) were applied, the accuracy of the proposed crop-weather models would be reduced. More importantly, the Matern 5/2 Kernel, which was the most suitable function in developing models for 6 regions in this research, was not recommended in previous related research studies [16][17][18][19]. The use of Exponential Kernel, which was found to be the best in developing models for the other 3 regions, was also not recommended by other researchers though it was used in previous research conducted by the authors [11].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…If one of the Kernel functions recommended in previous research studies (Exponential/ RBF /Squared Exponential) were applied, the accuracy of the proposed crop-weather models would be reduced. More importantly, the Matern 5/2 Kernel, which was the most suitable function in developing models for 6 regions in this research, was not recommended in previous related research studies [16][17][18][19]. The use of Exponential Kernel, which was found to be the best in developing models for the other 3 regions, was also not recommended by other researchers though it was used in previous research conducted by the authors [11].…”
Section: Discussionmentioning
confidence: 90%
“…Though they had used only the Radial Basis Function (RBF) and the Rational Quadratic Kernel, GPR and DNNR were reported to have performed well with R2 > 0.90. According to research on the paddy yield estimation in Nepal, GPR outperformed SVMR, Linear Regression, and Ridge Regression [18]. However, this study was limited to a single Kernel of Squared Exponential.…”
Section: Introductionmentioning
confidence: 99%
“…The 20 m bands were up-sampled to 10 m resolution using nearest-neighbor interpolation [39]. Bands 1, 9, and 10 at 60 m spatial resolution, dedicated to atmospheric correction and cirrus detection, were discarded [40,41].…”
Section: Data Source and Pre-processingmentioning
confidence: 99%
“…In recent years, deep learning models, such as convolutional neural networks (CNNs) and recurrent neural networks (RNNs), have provided strong technical support for crop mapping [33,34]. Kussul et al used 19 scenes of Sentinel-1A and Landsat-8 data and a shallow CNN for crop classification in Ukraine, which showed that the CNN architecture outperformed the multilayer perceptron architecture, resulting in accuracies above 85% for major crops [35].…”
Section: Introductionmentioning
confidence: 99%